PENGARUH METODE STRUKTURAL ANALITIK SINTETIK (SAS) TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI 79 PEKANBARU - Ulil Meisal; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the problem of the lack of students’ abilityof reading at the beginning, so it is necessary to apply SAS method in order to assiststudents in learning to get successful to read at the beginning. The purpose of this studyis to describe the effect of SAS method to students’ ability to read at the beginning in theexperimental class and to describe the differences about impoving students’ readingability at the begining that significant between students who acquire learning throughthe SAS method and students who received conventional learning. This study is a quasiexperimentalresearch with the research subjects are students of first grade at class IA,SD Negeri 79 Pekanbaru, this class contain of 28 students as control class and class IBof 28 students as the experimental class. The results state that in the pretest scores afteranalyzed by t meet the criteria tcount<ttable that is 0.001 <2.007, which means there is nodifference that significant and the first ability of students in the control and experimentclass are same. While on the posttest score after analyzed by t 'meet the criteria t'count>t’table that is 2.480> 2.007, which means that there are significant differences in thepost-test scores between the experimental class and control class. Based on thecoefficient of determination in the experimental class found great determinationcoefficient was 0.870, it means SAS method very influence on students' ability to read atthe beginning of the experimental class. Based on the index gain, improved readingability of students at the beginning of the experimental class has an average of 0.566with the medium category, and the control class 0.220 with low category, it means thatthere are differences of increased the ability to read at the beginning that significantbetween experimental class and control class.KeyWords: SAS method, the ability of reading at the beginning.